Global, regional, and national burden of cardiovascular diseases attributable to high body mass index from 1990 to 2021 - Yao, Liangtao; Hou, Wenying; Zheng, Yan; Su, Guohai (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIn recent decades, the escalating prevalence of obesity has contributed to a significant increase in the global burden of disease, with cardiovascular diseases (CVDs) emerging as the leading cause among all diseases attributable to high body-mass index (BMI). Utilizing global burden of disease (GBD) dataset from 1990 to 2021, we conducted a comprehensive analysis of the global, regional, and national trends in deaths and disability-adjusted life years (DALYs) attributable to CVDs caused by high BMI. Age-standardized mortality rate (ASMR) and age-standardized DALY rate (ASDR) were also investigated. Furthermore, we examined the associations of gender, age, and socio-demographic index (SDI) with the burden of CVDs attributable to high BMI. Finally, we assessed the evolution of health inequalities across countries and projected the global deaths and DALYs due to high BMI-related CVDs over the next two decades.MethodsThe absolute numbers and the rates of age-standardized death, Disability-Adjusted Life Years (DALYs) per 100,000 people due to high BMI-related CVDs between 1990 and 2021 were extracted from GBD 2021. The estimated annual percentage changes (EAPCs) of high BMI-related CVDs disease burdens were calculated under the GBD's comparative risk assessment framework. Additionally, the disease burden prediction of the high BMI-related CVDs from 2022 to 2041 was performed using the bayesian age-period-cohort (BAPC) statistical model.ResultsIn 2021, high BMI-related CVDs accounted for 1.90 million deaths globally, representing an increase of 120.63% compared to 1990, with DALYs rising by 115.47% over the same period. Notably, while ASMR and ASDR among male showed no decline, female experienced 11.30% reduction in ASMRs and 6.12% reduction in ASDR. The burden was disproportionately borne by middle-aged and older populations across all age groups. Global health inequalities related to high BMI-related CVDs demonstrated a narrowing trend from 1990 to 2010, followed by a reversal into a negative correlation and continued to widen until 2021. Looking ahead, the burden of high BMI-related CVDs is projected to rise significantly due to population growth, the increasing prevalence of obesity, and aging populations.ConclusionThe results indicate that from 1990 to 2021, the burden of CVDs caused by high BMI has significantly increased. Particular attention should be directed toward middle and low-middle SDI regions. To mitigate this burden, it is imperative to implement public health strategies that emphasize education and awareness regarding the correlation between high BMI and CVDs. Policies promoting healthy dietary habits and regular physical activity are essential for reducing the future impact of high BMI-related cardiovascular morbidity and mortality. Such measures are not only urgently needed but also offer substantial long-term benefits for global health.